Application of bioreactor design principles to plant micropropagation - Curtis, W.R.
Principles of oxygen consumption, oxygen transport, suspension, and mixing are discussed in the context of propagating aggregates of plant tissue in liquid suspension bioreactors. Although micropropagated plants have a relatively low biological oxygen demand (BOD), the relatively large tissue size and localization of BOD in meristematic regions will typically result in oxygen mass transfer limitations in liquid culture. In contrast to the typical focus of bioreactor design on gas-liquid mass transfer, it is shown that media-solid mass transfer limitations limit oxygen available for aerobic plant tissue respiration. Approaches to improve oxygen availability through gas supplementation and bioreactor pressurization are discussed. The influence of media components on oxygen availability are also quantified for plant culture media. Experimental studies of polystyrene beads in suspension in a 30-l air-lift and stirred bioreactors are used to illustrate design principles for circulation and mixing. Potential limitations to the use of liquid suspension culture due to plant physiological requirements are acknowledged.
Keywords: OXYGEN TRANSPORT; RESPIRATION; SOMATIC EMBRYOGENESIS; SUSPENSION CULTURE; TISSUE CULTURE